Performances of bicycle tyres - effect of vertical load and inflation pressure - Dell`Orto, G.; Mastinu, G. (Journal of Science and Cycling, 2023)
Tyre characteristics can strongly affect bicycle dynamics, therefore the overall bicycle performances. We already know the importance of longitudinal tyre characteristics (commonly known as rolling resistance), but the lateral characteristics are mostly ignored. Proper testing machines for bicycle tyres are required to measure the lateral characteristics, in order to have a full tyre characterization. The paper presents the results from an experimental campaign on road racing bicycle tyre. Vertical load may affect a lot the tyre parameters, as well as inflation pressure. Specifically, a variation in vertical load of 50 N may results also in 10% increase in cornering stiffness, the main parameter used to assess tyre lateral characteristics.